The use of oral glucose-lowering agents (GLAs) in β-thalassemia patients with diabetes: Preliminary data from a retrospective study of ICET-A Network: Oral glucose-lowering agents (GLAs) in β-thalassemia patients - De Sanctis, Vincenzo; Soliman , Ashraf; Tzoulis, Ploutarchos; Daar , Shahina; Kattamis, Antonis; Delaporta , Polyxeni; Karimi , Mehran; Yassin, Mohamed A.; Zarei, Tahereh; Saki, Forough; Sapunarova, Katia; Banchev, Atanas; et al. (Acta Biomedica Atenei Parmensis, 2022)
Objective: The management of prediabetes and hyperglycemia is an increasingly important aspect of care in patients with thalassemia. In light of the limited evidence about the management of GD (glucose dysregulation) with glucose-lowering agents (GLAs), we have conducted a retrospective survey in TDT and NTDT patients with diabetes mellitus to collect more detailed information on GLA use in order to make preliminary recommendations. Study design and method: A questionnaire was prepared and distributed to the tertiary thalassemia care Centers of ICET-A Network. Results: Eight  thalassemia care Centers [Bulgaria, Greece, Iran, Italy (4 Centers) and Qatar], following 1.554 with transfusion-dependent thalassemia (TDT), 132 (8.4%) with diabetes and 687 with non-transfusion-dependent thalassemia (NTDT), 27 (3.9%) with diabetes, participated in the retrospective survey. The records of 117 TDT patients and 9 NTDT patients with diabetes treated with GLAs were analyzed. Metformin, a biguanide, was the most frequently used drug (47.6 %), followed by alpha-glucosidase inhibitors (5.5 %), incretins (4.7%) and insulin secretagogues (3.1%).  In 68 (61.2) patients  GLAs was prescribed as monotherapy, while the remaining  49  (38.8%), who had inadequate glucose control with metformin, were treated with combination treatment. Fifty-one patients  of 126 (40.4%) initially treated with oral GLA, for a mean duration of 61.0 ± 35.6 months (range: 12- 120 months), required insulin therapy for better metabolic control. Conclusion: This retrospective study covers an unexplored area of research in patients with thalassemia and GD. Oral GLAs appear to be safe and effective for the treatment of diabetes mellitus in patients with thalassemia, and can achieve adequate glycemic control for a substantial period of time.